FERONIA functions through Target of Rapamycin (TOR) to negatively regulate autophagy - Wang, Ping; Clark, Natalie M.; Nolan, Trevor M.; Song, Gaoyuan; Whitham, Olivia G.; Liao, Ching-Yi; Montes-Serey, Christian; Bassham, Diane C.; Walley, Justin W.; Yin, Yanhai; Guo, Hongqing (Frontiers in Plant Science, 2022)
FERONIA (FER) receptor kinase plays versatile roles in plant growth and development, biotic and abiotic stress responses, and reproduction. Autophagy is a conserved cellular recycling process that is critical for balancing plant growth and stress responses. Target of Rapamycin (TOR) has been shown to be a master regulator of autophagy. Our previous multi-omics analysis with loss-of-function fer-4 mutant revealed that FER is implicated in autophagy pathway. We further demonstrated that the fer-4 mutant displayed constitutive autophagy, and FER is required for TOR kinase activity measured by S6K1 phosphorylation and by root growth inhibition assay to TOR kinase inhibitor AZD8055 in different genotypes. Taken together, our study provides a novel mechanism by which a plasma membrane-localized receptor kinase FER functions through TOR to negatively regulate autophagy.